Advanced exergy analysis applied to the process of regasification of LNG (liquefied natural gas) integrated into an air separation process. (15th December 2016) - Tesch, Stefanie; Morosuk, Tatiana; Tsatsaronis, George
Abstract: Natural gas is one of the most important sources of energy, the demand for which increases continuously. The LNG (liquefied natural gas) market rises currently exponentially; many countries entered this market recently. Applying an efficient regasification process for LNG is now more important than in the past. At present, mainly regasification of LNG via direct or indirect heating is used for industrial applications. Regasification of LNG can also be combined with generation of electricity. Another possibility is the integration of the regasification into a processes requiring low temperatures. A new concept dealing with the integration of regasification of LNG into a cryogenic process of air separation has recently been developed at Technische Universität Berlin. This paper evaluates two options of integrating the regasification of LNG into an air separation system. Conventional and advanced exergy analyses are used in the evaluation. Highlights: The integration of LNG regasification into an air separation process was studied. Two integrated designs with different exergetic efficiencies are discussed. Power consumption by the air separation unit decreases notably through integration. The advanced exergy analyses highlight components that are of particular interest. The effect of the pressure of LNG supply was investigated.